DECISION SUPPORT SYSTEM PRIORITAS PEMBANGUNAN JALAN DIDESA SEI ALIM ULU DENGAN METODE TOPSIS - Ningsi, Fitria; Wardani, Intan Kusuma; Siregar, Maya; Pramudja, Siska Damayanti (J-Com (Journal of Computer), 2023)
Abstract: Road construction infrastructure has an important role, especially in supporting the economic, social and cultural fields. Sei Alim Ulu Village is an area that is still lagging behind due to the lack of attention from the government, especially in terms of road construction. Road construction in the area can be said to be still bad, making it difficult for the community to do their activities. To facilitate the decision-making process related to development priorities in the village, a decision support system program was created. Decision support systems are systems that help users make decisions in a systematic process. Development priorities in the village are determined using the Topsis method. This study aims to obtain a decision model for the development of priority areas with criteria based on road damage, location requirements, cost estimates, road pavements, and road conditions. Of the 6 alternatives tested, v1 with a value of 0.6301303 obtained the highest score which means it is a priority area for road construction in Sei Alim Ulu Villag. Keywords : SPK; topsis method; village infrastructure  Abstract:Infrastruktur pembangunan jalan memiliki peranan penting terutama dalam mendukung bidang ekonomi, sosial dan budaya. Desa Sei Alim Ulu merupakan daerah yang masih tertinggal akibat kurangnya perhatian dari pemerintah terutama dalam hal pembangunan jalan. Pembangunan jalan di daerah tersebut bisa dibilang masih buruk sehingga menyulitkan masyarakat untuk beraktivitas. Untuk memudahkan proses pengambilan keputusan terkait dengan prioritas pembangunan didesa, maka dibuatlah program sistem pendukung keputusan. Sistem pendukung keputusan adalah sistem yang membantu pengguna membuat keputusan dalam proses yang sistematis. Prioritas pembangunan didesa ditentukan dengan metode Topsis. Penelitian ini bertujuan untuk memperoleh model keputusan pengembangan kawasan prioritas dengan kriteria berdasarkan kerusakan jalan, kebutuhan lokasi, perkiraan biaya, perkerasan jalan, dan kondisi jalan. Dari 6 alternatif yang diuji, v1 dengan nilai  0,6301303 diperoleh nilai tertinggi yang berarti Sebagai Kawasan prioritas pembangunan jalan di Desa Sei Alim Ulu. Kata Kunci : infrastruktur, metode topsis, SPK.